CPW-fed Dual band circular patch antenna with tapered and ridge ground for WiMAX/WLAN and UWB applications. - Suneel, E.; Prabhakara Rao, B. (International Journal of Engineering and Technology, 2018)
A coplanar wave guide (CPW)-fed dual band circular patch antenna with tapered and ridge ground is designed and its performance is verified experimentally for ultra-wideband (UWB) applications. The proposed antenna is compact in size has the overall dimensions (25x35x1.6) mm3 and fabricated on FR4 substrate. Ground of the antenna is tapered and ridged on either side to get the desired performances .The dual frequency circular patch antenna which exhibits wide frequency bands over the UWB range. Antenna has wide dual band ranging from 2.6–6.67GHz (87.8%) and 7.5–10.5GHz (33.3%).Antenna can provide omnidiretional radiation patterns, appropriate for (Worldwide interoperability for microwave access (WiMAX), Wireless local area network (WLAN) and UWB applications. Â Â